Occurrence and Abundance of Vibrio spp. in Traditional Shrimp Ponds of Tarakan, Indonesia: Implications for Aquaculture Biosecurity - Yusron, Muhammad; Maulianawati, Diana (Aquatic Life Sciences, 2026)
Shrimp aquaculture faces recurrent challenges from Vibrio spp., opportunistic pathogens that threaten production sustainability, particularly in traditional farming systems with limited management inputs. Despite the widespread assumption that Vibrio levels in traditional ponds generally remain below pathogenic thresholds, information on their temporal persistence and relationship with water quality remains limited. This study aimed to isolate and quantify Vibrio spp. in traditional shrimp ponds in Tarakan, Indonesia, and to evaluate their relationship with key water quality parameters. Water samples were collected biweekly from week 0 to week 10 at three sampling stations in each of two ponds. Vibrio spp. were isolated using Thiosulfate Citrate Bile Salt Sucrose Agar (TCBSA), and Total Vibrio Counts (TVC) were expressed as colony-forming units per milliliter (CFU/mL). Physicochemical parameters, including temperature, pH, salinity, and dissolved oxygen (DO), were measured concurrently. The results showed that Vibrio colonies were consistently detected throughout the culture period, with abundances ranging from 1.5 × 10¹ to 2.6 × 10³ CFU/mL in Pond 1 and 2.4 × 10¹ to 1.2 × 10³ CFU/mL in Pond 2, remaining below the pathogenic threshold of 1 × 10⁴ CFU/mL. Water quality parameters remained within optimal ranges (temperature 31.4–32.0 °C, pH 7.3–7.8, salinity 17–18 ppt, DO 5.3–5.9 mg/L). Pearson correlation analysis showed weak and non-significant relationships between Vibrio abundance and the measured environmental variables. These findings suggest that Vibrio persistence in traditional shrimp ponds may be influenced by factors beyond physicochemical water quality. Continuous monitoring of Vibrio abundance is therefore important to support disease prevention and biosecurity management in traditional shrimp aquaculture systems.